In Vitro Alpha-Glucosidase Inhibitory Effect of Etlingera Elatior Ethanol Extract Growing in Gayo Highland, Aceh Province, Indonesia [version 2; peer review: 2 approved] - Milda Husnah; Saudah Saudah; Nuzul Asmilia; Zumaidar Zumaidar (F1000Research)
Background The prevalence of diabetes mellitus (DM) is increasing overtime, potentially leading to various severe health complications and mortality. Despite therapeutic agents have currently been developed, unexpected adverse effects are inevitable. Hence, safe and effective medications such as those of plant origin are critical to prevent unexpected complication in DM sufferers. Etlingera elatior has been widely used as spice and traditional medicine to treat diabetes in Aceh Province, Indonesia. However, study regarding α-glucosidase inhibitory effect of E. elatior growing in Gayo highlands, Aceh, Indonesia, is completely lacking. The aim of this study was to evaluate in vitro α-glucosidase inhibitory effect of E. elatior ethanol extracts (EEEE) growing in Gayo highlands, Aceh Province, Indonesia. Methods Antioxidant activity was determined using DPPH procedure, whereas α-glucosidase inhibition assay was carried out using spectrophotometric method. Data analysis was performed using One-Way Analysis of Variance (ANOVA), followed by Duncan’s multiple range test at α=0.05. Results Phytochemical analysis revealed the presence of total phenolic (TPC), total flavonoid (TFC), and total tannin (TTC) content in all E. elatior plant parts, in which the highest TPC was found in the stem (158.38 GAE/g), whereas the highest TFC and TTC was obtained in the rhizome extracts. The extract of fruit showed the strongest antioxidant activities, followed by the stem and leaf, with IC50 of 2.381 μg/mL, 6.966 μg/mL, and 19.365 μg/mL, respectively. All E. elatior extracts revealed a significant inhibitory activity against α-glucosidase at the concentration of 500 μg/mL, in which the stem extract showed the most effective α-glucosidase inhibitory effect with IC50 value of 5.15 μg/mL, suggesting its promising potential as antidiabetic agent. Conclusions This study highlights E. elatior potency as a novel source of antioxidant and natural antidiabetic compounds that are useful for the prevention and treatment of diabetes.